Development of a Beverage that Forms a Bubble-Containing Gel in the Stomach and Evaluation of its Gastric Digestion Behavior - KOBAYASHI, Isao; ICHIKAWA, Sosaku; DOMOTO, Takashi; KOZU, Hiroyuki (Japan Journal of Food Engineering, 2025)
Obesity prevention is crucial for controlling lifestyle disease and extending healthy life expectancy. Focusing on the appetite suppression by gastric wall stretching, the company affiliated with the first author developed and evaluated a carbonated beverage that forms a bubble-containing gel under the acidic conditions of gastric juice. A carbonated beverage containing pectin was developed from the viewpoints of easy to intake, stability, and convenience. The findings were obtained regarding the state of the bubble-containing gel in the human stomach and the improvement of satisfaction. Next, we conducted an in vitro evaluation of the bubble-containing gels using the Gastric Digestion Simulator that simulates gastric peristalsis. The results of the analysis indicated that low esterification/high amidation pectin and low citric acid concentration in the beverage improved the swelling and stability of the bubble-containing gel. In 2014, the company affiliated with the first author launched a beverage that forms a bubble-containing gel in the stomach. The results of this study were used for product renewal after 2018.